Study on the sorption process of triclosan on cationic microfibrillated cellulose and its antibacterial activity. (20th January 2016) - Zhang, Hongjie; Zeng, Xu; Xie, Jinglei; Li, Zhiqiang; Li, Hailong
Highlights: The CMFC was firstly assembled by the TCS, for introducing antibacterial activity. The adsorption process of TCS onto CMFC was controlled by chemisorptions. The isotherm models showed that CMFC had a great adsorption ability to TCS. A novel antibacterial cellulose-based TCS/CMFC compound was produced successfully. Abstract: Cationic microfibrillated cellulose (CMFC), as one kind of cellulose-based materials, is widely used in many fields. In this work, it was functionalized with a traditional antibacterial agent (triclosan, TCS). The sorption process of TCS onto CMFC was expressed by kinetic and isotherm models. The results showed that there was a high correlation coefficient ( R 2 > 0.9) in the pseudo-second-order model and the isotherm models, indicating that CMFC had a good sorption capacity for TCS. The sorption type was chemisorption, and the reaction power was electrostatic interactions. The antibacterial activity of the assembled TCS/CMFC compound was tested by disk diffusion method, and it was found a higher antibacterial activity than CMFC alone (bigger inhibition zone diameters). Further, the functionalized TCS/CMFC compound was used in the fiber network during handsheets making, and it had a higher antibacterial rate than TCS alone (increase by 45.1% against Escherichia coli and by 54.8% against Staphylococcus aureus, respectively).